Synthesis and characterization of mixed ligand catecholato-bis (diamine-mono-dithiocarbamato) vanadium (IV) complexes - Begum, B; Sarker, A; Rahman, AKM Lutfor; Bhoumik, NC (Bangladesh Journal of Scientific and Industrial Research, 2017)
Diamine-mono-dithiocarbamates are mono-basic bidentate ligand forming stable complexes with transition metals. Mixed ligand catecholato-bis (diamine-mono-dithiocarbamato) vanadium (IV) complexes were synthesized and characterized using FT-IR, UV-visible and 1H-NMR spectroscopic techniques. The formation of vanadium complexes was con?rmed by the disappearance of ?S-H band in the complexes which was present in the ligands and incidence of ?V-S and ?V-O band in FT-IR spectra of the complexes. The mono-dithiocarbamate with one uncoordinated ?NH/NH2 group was indicated by the presence of ?N-H vibrational band in both the ligands and complexes. In the 1H-NMR spectra, the peak for SH proton of ligands disappeared in the complexes suggest the formation of [VL2Cat] complex. Non-electrolytic nature of the synthesized complexes was established by their low molar conductance values. The +4 oxidation state of vanadium was con?rmed by the electronic spectra of the complexes. On the basis of all physico-chemical data, a six-coordinated octahedral structure has been suggested for catecholato-bis (diamine-mono-dithiocarbamato) vanadium (IV) complexes. Bangladesh J. Sci. Ind. Res. 52(2), 89-96, 2017